2009
DOI: 10.1002/eji.200839214
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial IQGAP1 regulates efficient lymphocyte transendothelial migration

Abstract: Leukocyte movement from the blood to the tissues is a fundamental process in acute and chronic inflammatory diseases. While the role of endothelial cells (EC) to recruit leukocytes to sites of inflammation is well known, the mechanisms that control remodeling of EC shape and adhesive contacts during leukocyte transendothelial migration (TEM) are not completely understood. We studied the role of IQGAP1, an adaptor protein that binds to filamentous-actin and microtubules (MT) at interendothelial junctions, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
(98 reference statements)
5
17
0
Order By: Relevance
“…Comparatively few studies have examined the endothelial actions of IQGAP1, 27, 29, 37-39 and no prior experiments have established a link between IQGAP1 and endothelial barrier function. Yamaoka-Tojo, et al, elegantly showed how IQGAP1 functions as a VEGFR2-associated scaffold protein that enables VEGF-induced migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively few studies have examined the endothelial actions of IQGAP1, 27, 29, 37-39 and no prior experiments have established a link between IQGAP1 and endothelial barrier function. Yamaoka-Tojo, et al, elegantly showed how IQGAP1 functions as a VEGFR2-associated scaffold protein that enables VEGF-induced migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Both events are critical for capillary tube formation, implicating IQGAP1 in angiogenesis. A later study (75) observed enrichment of IQGAP1 at junctions of human endothelial cells, but failed to detect any change in VE-cadherin at junctions when IQGAP1 was knocked down. The authors speculate that differences in cell confluence accounted for the variable findings, but further research is necessary to reconcile these seemingly discrepant data.…”
Section: Iqgap1 Binding Partnersmentioning
confidence: 97%
“…IQGAP was shown to regulate junction remodeling in a microtubule-dependent fashion. Downregulation of IQGAP caused a strong reduction in lymphocyte transendothelial migration (58). In contrast, VE-cadherin, which is not included in the LBRC and does not serve as a counterreceptor for transmigrating leukocytes, needs to be moved out of the way.…”
Section: Different Abps Act During Different Steps Of the Leukocyte Ementioning
confidence: 98%